2023
DOI: 10.3390/educsci13040377
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions and Attitudes of Pre-School and Primary School Teachers towards STEAM Education in Spain

Abstract: STEAM education postulates integrated problem-solving-based learning of its disciplines. Although positive results are being reported, there are some difficulties with its implementation. The purpose of this research is to analyze the conceptions and attitudes of Early Childhood and Primary School teachers in Spain towards this educational approach, as well as to determine the initial relationship with their training and experience. A multiple case study with 11 teachers was conducted using a reflection protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
3
0
3
Order By: Relevance
“…De manera similar, este resultado respalda las conclusiones , quienes desmienten "los argumentos sobre la supuesta incapacidad de los futuros maestros para formarse en enfoques integrados, mostrando que incluso experiencias cortas, pero coherentes y basadas en las mejores evidencias científicas disponibles, pueden ser eficaces" (p. 104). Por último, estos resultados refuerzan la necesidad y la viabilidad de la formación en enfoques integrados para los futuros profesores, como indican Ortiz-Revilla et al (2023).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…De manera similar, este resultado respalda las conclusiones , quienes desmienten "los argumentos sobre la supuesta incapacidad de los futuros maestros para formarse en enfoques integrados, mostrando que incluso experiencias cortas, pero coherentes y basadas en las mejores evidencias científicas disponibles, pueden ser eficaces" (p. 104). Por último, estos resultados refuerzan la necesidad y la viabilidad de la formación en enfoques integrados para los futuros profesores, como indican Ortiz-Revilla et al (2023).…”
Section: Discussionunclassified
“…La educación STEM/STEAM ha adquirido un creciente nivel de relevancia porque la tecnología y la innovación se perciben como elementos clave para el progreso económico y social (Mpofu, 2020). En el ámbito educativo, esta apuesta sigue ocupando una posición central (Grimalt-Álvaro y Couso, 2022;Ortiz-Revilla et al, 2023) porque ofrece un enfoque pedagógico fundamentado en metodologías activas que no solo promueven la integración y transferencia de conocimientos, sino que fomentan el aprendizaje contextualizado y la interdisciplinariedad (Ortiz-Revilla et al, 2021).…”
Section: El Aprendizaje De Stem/steam a Través Del Aicleunclassified
“…According to Jiménez-Tejada et al (2016), Spanish early childhood educators have similar perceptions of science and science activity implementation to U.S. educators. Ortiz-Revilla et al (2023) found a number of Spanish early childhood teachers have a conceptual understanding of science concepts, including STEAM, and that early science experiences are linked to real-world experiences. Many Spanish teachers also recognize that science inquiry develops at an early age, but they often feel uncertain about teaching science to young children (Jiménez-Tejada et al, 2016).…”
Section: Teacher Knowledge Attitudes and Beliefsmentioning
confidence: 99%
“…However, educational systems in Europe face strong hurdles in fulfilling this aim. These range from a low percentage of teachers choosing STEM as their teaching subjects, general teacher shortages, and teachers' critical attitudes toward STEM (Ortiz-Revilla et al, 2023). Given this context, a training concept for pre-and in-service teachers in Austria was developed that focuses on STEM instruction 2 / 13 in elementary education (age range six to ten).…”
Section: Introductionmentioning
confidence: 99%